Influence of A-Site Deficiency and Ca Concentration on the Electrical and Crystallographic Properties of (Nd0.2Sr0.7–xCax)yTi0.95Fe0.05O3−δ-Based Fuel Electrode for Solid Oxide Cells - Paydar, S.; Kooser, K.; Volobujeva, O.; Granroth, S.; Nurk, G. (American Chemical Society, 2025)
This study explores the impact of A-site deficiency and Sr/Ca ratio on the electrochemical and crystallographic properties of a (Nd0.2Sr0.7–xCax)yTi0.95Fe0.05O3−δ hydrogen electrode for solid oxide cells under reducing and air atmospheres. 5\% and 10\% A-site deficient (Nd0.2Sr0.7–xCax)yTi0.95Fe0.05O3−δ (x = 0.35–0.45, y = 1.05, 1) (referred to as 5NSCTF-x and 10NSCTF-x) materials were studied, while the ratio between A-site cations was kept the same with both deficiencies. The results demonstrate that the extent of A-site deficiency and the Ca concentration in the A-site have a significant impact on the microstructure (sinterability), conductivity, and catalytic activity of electrodes. Segregation of Nd from the lattice with 5\% A-site deficiency was observed as a result of thermal treatment at low pO2. Among the studied materials, the highest total electrical conductivity of porous electrode layer at 850 °C and in 97\% H2 + 3\% H2O atmosphere was 4.8 S cm–1 observed for the Nd0.2Sr0.35Ca0.35Ti0.95Fe0.05O3−δ (10NSCTF-35). The highest electrochemical performance was observed in the case of Nd0.2Sr0.25Ca0.45Ti0.95Fe0.05O3−δ (10NSCTF-45), which showed a polarization resistance value equal to 0.19 Ω cm2 after 100 h of stabilization at 800 °C in a humidified (1.7\% H2O) H2 atmosphere. The best electrochemical performance with 606 mW cm–2 power density at 850 °C in 98.3\% H2 + 1.7\% H2O atmosphere was demonstrated by a 50 wt \% Nd0.2Sr0.25Ca0.45Ti0.95Fe0.05O3−δ + 50 wt \% Ce0.9Gd0.1O2−δ composite.